The interactions between oral-gut axis microbiota and Helicobacter pylori - Xi Chen; Xi Chen; Nanxi Wang; Jiannan Wang; Binyou Liao; Lei Cheng; Lei Cheng; Biao Ren (Frontiers in Cellular and Infection Microbiology, 2022)
In the human body, each microbial habitat exhibits a different microbial population pattern, and these distinctive microflorae are highly related to the development of diseases. The microbial interactions from host different niches are becoming crucial regulators to shape the microbiota and their physiological or pathological functions. The oral cavity and gut are the most complex and interdependent microbial habitats. Helicobacter pylori is one of the most important pathogens from digestive tract, especially the stomach, due to its direct relationships with many gastric diseases including gastric cancer. H. pylori infections can destroy the normal gastric environment and make the stomach a livable channel to enhance the microbial interactions between oral cavity and gut, thus reshaping the oral and gut microbiomes. H. pylori can be also detected in the oral and gut, while the interaction between the oral-gut axis microbiota and H. pylori plays a major role in H. pylori’s colonization, infection, and pathogenicity. Both the infection and eradication of H. pylori and its interaction with oral-gut axis microbiota can alter the balance of the microecology of the oral-gut axis, which can affect the occurrence and progress of related diseases. The shift of oral-gut axis microbiota and their interactions with H. pylori maybe potential targets for H. pylori infectious diagnosis and treatment.